Lu Shiyong’s Interpretation of the Nature and Artistry of A Verse in “Nine Songs” - Xiaoqiang, WANG (International Journal of Sino-Western Studies, 2023)
Lu Shiyong(1591?—1642?) put forward the claim that A Verse in “Nine Songs” is “not a piece of a funeral oration”. Lu proposed that it is a lyrical verse and elaborated on it in terms of the theme, the relationship between humans and the gods, and the background of the work. He held that A Verse in “Nine Songs” has the characteristics of “being elegant and pathetic”, reflected in it has “short sentences and long rhymes” and “an elegant context”. The general characteristics of A Verse in “Nine Songs” is that its language is concise and its semantics natural and simple. Lu explained his view of A Verse in “Nine Songs” having “an elegant context”, in terms of the emotional charm, the mingling of the emotions and the scenery, and the mastery of expressing feelings via verse, and thus expanded the area of research of his poetry theory.